India's Investment Climate : Voices of Indian Business - Ferrari, Aurora (Washington, DC: World Bank, 2012)
This book identifies key investment climate bottlenecks that slow down growth and poverty reduction. Based on face-to-face surveys of owners and managers of firms, combined with extensive dataset analysis, backed by secondary sources, the study analyses the critical factors that influence day-to-day decisions by firms on how to invest. As a result, it identifies growth-enabling reforms that cover macroeconomic policies, governance, institutions, and infrastructure. To get an understanding of investment climate constraints for the entire economy, the book focuses on four key sectors. The manufacturing sector, both organized and unorganized, is important in that it not only contributes a significant share of the overall gross domestic product (GDP), but it is also critical for employment generation and to the growth of the 'lagging' states. Similarly, the retail sector is an important part of the overall economy in its contribution to GDP and to employment. Finally, the information and communication technologies (ICT) sector, though a small part of GDP, has been leading India's services success story and serves as a good example from which the authors may learn. The book presents illustrative case studies of the key constraints identified, and the efforts to address them, along with policy recommendations. Furthermore, the book identifies a number of issues that require further analysis; in those instances the book should be viewed as a first step to bringing the issues into the forefront. The World Bank Group stands ready to work with the government, private sector, and other stakeholders in taking forward this work to help generate real impact on the ground.